2007
DOI: 10.1016/j.hlc.2007.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Resistance

Abstract: Clopidogrel resistance has been used as one of the terms employed in the literature to describe different degrees of ex vivo low platelet inhibition after clopidogrel administration. In addition to the diverse nomenclature, the characterisation of clopidogrel resistance has also been problematic because different authors have given different definitions. The mechanisms responsible for this decreased platelet response are not yet clearly defined, some hypotheses have been put forward but not yet demonstrated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 84 publications
1
16
0
1
Order By: Relevance
“…Several previous studies demonstrated anti--inflammatory effect of low doses of ASA and clopidogrel, mainly in patients with CAD [18][19][20][21][22][23][24][25]. The results of subanalysis of Physician's Health Study suggested that cardioprotective effect of ASA correlated with its anti-inflammatory effect [26].…”
Section: Discussionmentioning
confidence: 95%
“…Several previous studies demonstrated anti--inflammatory effect of low doses of ASA and clopidogrel, mainly in patients with CAD [18][19][20][21][22][23][24][25]. The results of subanalysis of Physician's Health Study suggested that cardioprotective effect of ASA correlated with its anti-inflammatory effect [26].…”
Section: Discussionmentioning
confidence: 95%
“…Doses higher than 600 mg did not lead to more antiaggregation, since these doses did not lead to an increase in the concentration of the active metabolite 4 .…”
Section: Introductionmentioning
confidence: 90%
“…Thus, though not capable of sustaining platelet aggregation, they contribute to collagen-induced activation 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations